The fairytale life of Dorothy Gale - Kantra, Virginia (Berkley, 2023)
"Dorothy (Dee) Gale is searching for a place to belong. After her mother's death, Dee and her sister Toni settled with Uncle Henry and Aunt Em in Kansas, and Dee attended the University of Kansas. But after falling in love with and subsequently being humiliated by an adjunct faculty member and novelist, Dee is unable to face him-and the rest of the school-and applies to the writing program at Trinity College Dublin. At Trinity, Dee finds solace in a new group of friends: Sam Clery, who dropped out of college and now runs a newsagents ("No brains," his sister says). Dee discovers he is articulate and well-read-also hot, in a dissolute, Irish poet kind of way. Tim Woodman, who refused to take back his ex-fiancée ("You have no heart," she accuses). Not relationship material, Dee concludes. Plus, he's so stiff she thinks he doesn't like her. And Reeti Kaur, who is kindhearted but too afraid to tell her parents she wants to teach underprivileged girls rather than obtain her MBA and work in the family business ("I basically have no courage," she says). Throughout the semesters, the friends grow closer and encounter new opportunities, love, and heartbreak. Dee is faced with a choice that could dictate her future, but she still has feelings of doubt and insecurity. While she doesn't know where she belongs or what she truly wants, she is ready to make that decision-they say there's no place like home, but Dee comes to realize that wherever she ends up in the world will be where she's meant to be"--